A novel homozygous keratin 10 mutation in siblings with autosomal recessive epidermolytic ichthyosis. (October 2010) - Balasubramanian, Meena; Terron-Kwiatkowski, Ana; Shah, Manu; Wagner, Bart E; Mechan, Dot; Baty, David; Sobey, Glenda J
Epidermolytic hyperkeratosis (EHK; OMIM 113800), or epidermolytic ichthyosis (EI), is a rare autosomal dominant skin disorder characterized by erythroderma and blistering at birth, which is replaced by progressive hyperkeratosis. In most cases, EHK/EI is due to dominant mutations in the genes encoding keratin 1 or keratin 10. A recessive form of EHK/EI has been described caused by truncating mutations in the KRT10 gene. Here, we report two male siblings with EHK/EI in whom we have identified a novel homozygous mutation, KRT10 c.1A>T. We discuss the importance of establishing the mode of inheritance in EHK. We also discuss the varying presentation of a 'collodion baby', and the differential diagnosis to consider. The histopathological and ultrastructural changes in both forms of EHK/EI have subtle differences that are detailed, and the importance of identifying these key features to target molecular analysis is further explained. These cases highlight the value of a dedicated skin genetics clinic with high-quality histopathological and electron microscopy services in the diagnosis of inherited skin conditions.